2012
DOI: 10.2147/clep.s28312
|View full text |Cite
|
Sign up to set email alerts
|

Use of prescription paracetamol during pregnancy and risk of asthma in children: a population-based Danish cohort study

Abstract: PurposeUse of paracetamol during pregnancy may increase the risk of asthma in offspring. The association between prenatal exposure to maternal use of paracetamol and risk of asthma was investigated.MethodsA cohort study of 197,060 singletons born in northern Denmark in 1996–2008 was conducted, with follow-up until the end of 2009. Maternal paracetamol use during pregnancy was defined as a redeemed prescription. Asthma in offspring was defined as at least two prescriptions of both a β-agonist and an inhaled glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 46 publications
0
37
1
Order By: Relevance
“…Five cohort studies,23 32–35 that measured wheeze outcomes before the age of 5 years, two cohort studies that measured paracetamol exposure during adulthood,36 37 and three RCTs,38–40 that did not measure incident asthma were subsequently excluded. Of the remaining 11 studies (representing 10 cohorts) included in the meta-analysis, all were observational cohort studies, five measured paracetamol exposure during pregnancy,13 41–44 one measured exposure during both pregnancy and infancy,14 and five measured exposure during infancy15 30 45–47 (table 1). The age at which outcome of asthma was measured ranged from 5 to 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five cohort studies,23 32–35 that measured wheeze outcomes before the age of 5 years, two cohort studies that measured paracetamol exposure during adulthood,36 37 and three RCTs,38–40 that did not measure incident asthma were subsequently excluded. Of the remaining 11 studies (representing 10 cohorts) included in the meta-analysis, all were observational cohort studies, five measured paracetamol exposure during pregnancy,13 41–44 one measured exposure during both pregnancy and infancy,14 and five measured exposure during infancy15 30 45–47 (table 1). The age at which outcome of asthma was measured ranged from 5 to 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…A weak association between paracetamol exposure during the third trimester of pregnancy and childhood asthma was shown by two studies (pooled OR=1.17, 95% CI 1.04 to 1.31, figure 2), while the three other studies that examined paracetamol exposure during the second and third trimester showed a stronger association (pooled OR=1.49, 95% CI 1.37 to 1.63, figure 2). There was significant heterogeneity among the three studies that assessed associations with paracetamol use through the entire pregnancy (Andersen et al ,13 OR=1.65, 95% CI 1.17 to 2.32; Rebordosa et al ,43 OR=1.22, 95% CI 1.11 to 1.34; Kang et al ,42 OR=0.74, 95% CI 0.5 to 1.09; I 2 =89%), so results were not pooled (figure 3). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm birth has been associated with increased childhood morbidity, among other things like childhood asthma . Some studies have found an association between maternal use of paracetamol (acetaminophen) with an increased risk of asthma , and one study described a link between maternal use of gastric acid–suppressive drugs and childhood asthma.…”
mentioning
confidence: 99%
“…Andersen et al showed that exposure to paracetamol within 30 days prior to the first menstrual period increased the risk of childhood asthma. This association was also found for 1 year after birth, and the authors could not rule out the noncausal explanations of their findings …”
Section: Discussionmentioning
confidence: 78%